Het ons te gou weggekyk? Nuwe belangstelling in die Hemelvaart en Sessio van Jesus - C. W. Burger (Acta Theologica)
In the last decade, after years of neglect, quite a number of interesting books about the Ascension and Sessio of Christ were published. One thinks especially about the contributions of Farrow, Dawson, Redding and Burgess. The aim of the article is to have a closer look at the publications, to ask for reasons for the new interest and to question progress in the discussion about the two themes evaluatively.